LONGICORN BEETLES AND THEIR DIET BREADTH FROM FORESTS OF KOLHAPUR DISTRICT, NORTHERN WESTERN GHATS, MAHARASHTRA - G. P. BHAWANE; Y. B. GAIKWAD; S. M. GAIKWAD; A. B. MAMLAYYA (The Bioscan, 2015)
Signs of wood and bark boring activity and Cerambycidae larvae in living and felled forest trees were discovered during Spetember- October 2010 in the forests of Kolhapur district, Northern Western Ghats Maharashtra with a new host plant record. Prompted by this result, we conducted a field study to determine the complex assem- blage of bark and wood boring longhorn beetles and their breadth of diet with distribution in the forests of Kolhapur district. Adult specimens were collected by caging infested bole samples under the laboratory condi- tions as well as by applying light trap near the selected sampling sites in the forests of Kolhapur district. A total of 26 species were recorded during the study period under 23 genera distributed in 4 subfamilies of family Cermabycidae viz. Prioninae, Lepturinae, Cerambycinae and Lamiinae from the forest area of Kolhapur district, Maharashtra, India. The beetles of economic importance are Aeolesthes holosericea, Xystocera globosa, Olenocamptus bilobus, Coptops aedificator, Batocera rufomaculata, Diorthus simplex, Plocaederus obesus, Celosterna scabrator, Stromatium barbatum and Xylotrechus subscutellatu. These species were recorded as major wood borer species in the forests of Kolhapur district. Cleonaria bicolor is being reported for the first time from this region of Western Ghats Maharashtra.